2018
DOI: 10.1093/jac/dky018
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies in national time trends of outpatient antibiotic utilization using different measures: a population-based study in France

Abstract: Time trends in outpatient antibiotic utilization expressed as PrID, DID, PID and SID provided conflicting results. We caution against using DID alone when monitoring antibiotic utilization. Instead, we recommend monitoring both DID and PrID as they provide different types of relevant information, especially when studying trends at a national level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…The prevalence rate of psychotropic drug use according to socio‐professional characteristics was only reported in the 2010 survey, showing an annual prevalence rate of 16.7% for the active adult population, with a higher prevalence rate in women compared to men, whatever the socio‐professional category 15 . Some studies performed on health care databases or with sales data have already identified a decrease in the use of antibiotics, 16,17 or of benzodiazepines and z drugs, 18 confirming the strong tendency observed in our study (and confirmed again between 2006 and 2016). The study by Airagnes et al used the data of the CONSTANCE cohort, a national population‐based cohort of randomly recruited participants, including volunteers aged 18–69 years at baseline in 22 selected health screening centers from the principal regions of France 6 .…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence rate of psychotropic drug use according to socio‐professional characteristics was only reported in the 2010 survey, showing an annual prevalence rate of 16.7% for the active adult population, with a higher prevalence rate in women compared to men, whatever the socio‐professional category 15 . Some studies performed on health care databases or with sales data have already identified a decrease in the use of antibiotics, 16,17 or of benzodiazepines and z drugs, 18 confirming the strong tendency observed in our study (and confirmed again between 2006 and 2016). The study by Airagnes et al used the data of the CONSTANCE cohort, a national population‐based cohort of randomly recruited participants, including volunteers aged 18–69 years at baseline in 22 selected health screening centers from the principal regions of France 6 .…”
Section: Discussionsupporting
confidence: 91%
“…They all had a high training in diagnoses of infectious diseases and they rigorously followed the guidelines for ATB prescriptions or RDT use. 36 In the coming months, other diagnostic tools must be deployed to improve the quality of diagnosis. These tools allow for adapted children management as well as improvement of the surveillance system.…”
Section: Discussionmentioning
confidence: 99%
“…The irrational use of antibiotics is a public health problem and has an impact on people’s health and economic development [ 1 3 ]. In the 1990 s, many countries, such as the United States, launched antimicrobial stewardship programmes [ 4 , 5 ] to promote the rational use of antibiotics.…”
Section: Introductionmentioning
confidence: 99%